Performance of Penaeusindicus, Cultured Under Three Salinities with Diet Containing Varying Energy Levels and Kilka, Clupeonella Delicatula, Oil Supplementation in the North of Persian Gulf, I.R. Iran - Yazdani Jahromi, Abdul Hamid (2001)
The effects of varying energy and kilka oil levels on the performances of Indian prawn Penaeus indicus were evaluated in a 35 day experimental period in three water salinities (25, 35 and 45 ppt). For each salinity, four experimental diets with energy levels of 3500, 3800,4 1 00 and 4400kcallkg, each containing three kilka (C/upeonel/a de/icatu/a) oil levels of 2, 4, 6% (totaling 1 2 experimental diets) were fonnulated using Lindo softwear program. All diets were isonitrogenous (40% protein) and fed at 8 percent of body weight to 3 6 groups of 200 juvenile shrimps (P. indicus) in each level of salinity. The results showed that under 25 ppt salinity, the diet containing 4 100 kcaV kg with 4% kilka oil showed the best results. For 35 ppt, 3800 kcaV kg with kilka oil level of 6 % was the suitable energy level. At 45 ppt, the best result was observed for the shrimp fed with 3500 kcall kg at 6% kilka oil level. It thus appeared that energy requirement vary with salinity. It also revealed that the energy to protein ratio of 1 1 0-1 1 8 kcaU g proteins was the most suitable ratio for the growth of the shrimp under different salinities. The incorporation of kilka oil in the diet as a source of energy and essential fatty acids showed a satisfactory growth performance of the prawn. The n-3 fatty acid of shrimp body tissue increased with the increasing the dietary n-3 fatty acid levels.